Penyuluhan Kesehatan Tentang Asma Di Desa Kampung Baru Kecamatan Tonjong Kabupaten Brebes - Ahmad Zakiudin; Esti Nur Janah; Tati Karyawati; Siti Fatimah; Aas Naita (Pusat Riset dan Inovasi Nasional, 2021)
Asthma is a heterogeneous disease characterized by chronic inflammation of the airways. This disease is diagnosed based on a history of respiratory symptoms such as wheezing, shortness of breath, a feeling of heaviness in the chest and coughing that varies in time and intensity, accompanied by limited expiratory air flow. The aim of this activity is to be able to understand asthma and administer simple steam inhalation to determine the effectiveness of airway clearance after administering inhalation therapy (UAP) to asthma patients. Health education about asthma and simple steam inhalation can increase the knowledge of Kampung Baru village residents to do their best to treat asthma using traditional medicine. Health education to residents can increase their knowledge and skills in using traditional drugs in a simple way.